Morphophysiological Changes Of Mungbean Under Different Water Regimes - Nazran, A; Ahmed, JU; Karim, AJMS; Ghosh, TK; Husna, T (Bangladesh Journal of Agricultural Research, 2023)
Drought stress can severely affect crop growth and productivity by altering several physiological processes. This experiment was carried out to explore the drought tolerance ability of four mungbean varieties based on their water relation and performance of some growth parameters. The experiment was conducted in pot at Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Gazipur from 27th March to 15th May 2017, under a semi-controlled (vinylhouse) condition. Three different water regimes 50 to 60% field capacity (FC), 70 to 80% FC, 90 to100% FC and four mungbean varieties namely BARI Mung-5, BARI Mung-6, BU mug 2, BU mug 4 were used as treatment variable. Among the three water regimes, 50%-60% FC was considered as the severe drought stress. Results indicated significant variations in different traits of both water and growth parameters of the varieties under severe drought stress (50%-60% FC). Among the four mungbean varieties BARI Mung-6 showed superior performance with higher xylem exudation, chlorophyll content, shoot dry matter and lower water uptake capacity at 50%-60% FC (severe drought stress) whereas BU mug 2 showed the lowest performance. Results of this experiment conclude that BARI Mung-6 can be considered as a more water stress tolerant variety than the other three and recommended for cultivation under water limited conditions. Bangladesh J. Agril. Res. 47(3): 257-267, September 2022